O personal trainer: uso de estrat??gias de marketing na atividade profissional - Spacov, Yuri Figueredo (2016)
We live in a time in which services tend to be exclusive and personalized. This context favors the insertion of Personal Trainer in the daily lives of people who are looking for style healthier life, which increases the supply of this service in the market and makes the competitive landscape in terms capitation customers. Thus, it is essential that professionals in this area to use marketing techniques to not only show what they do, but to differentiate and attract more consumers interested in their services. This work aimed to analyze how the Personal Trainer uses the marketing dissemination and promotion of its activities, and to evaluate the degree of importance of marketing in the process, raise the marketing strategies used to promote their services and identify the academic education contributes to the use of marketing strategies. The study is qualitative, exploratory and used a semi-structured interview to 15 Personals Trainers who work in the city of S??o Paulo. Data were categorized with the help of software ATLAS.ti 6.2 through content analysis and the results generated suggest that the Personal Trainer uses communication as greater dissemination strategy and promotion of their services, and the mouth marketing to mouth, display and social networks - Facebook, Instagram and Whatsapp - its main means to reach customers. Respondents understand the importance of marketing and management to manage his career, however 80% said that graduation did not offer enough content to work as a Personal Trainer.